(untitled) (American Journal of Interdisciplinary Research and Innovation, 2022)
Sri Lanka has approved a four-day work week to prepare better the public sector workers for the biggest financial crisis of the nation has seen in decades. The idea tries to encourage employees to engage in farming as the nation struggles to pay for essential imports like fuel, food, and medication. Most employees are still working even in declared national holiday Friday. This is because of four working days are not enough to finish their tasks. People waited longer in gas lines, which made it difficult for the country’s workforce to arrive for duty on time and in a productive manner. There are few public and private transportation options, which lengthens travel times for employees. Additionally, workers must pay high travel expenses, which raises their cost of living. Moreover, the employees stuck in traffic and unable to manage the crowded public and private transport facilities led them stress at work. As a result, people must balance job and personal obligations. This study was aimed to measuring the level of work-life balance among employees who were working in government schools, divisional secretariat, and hospital. A total of 120 employees were selected using random sampling method from government schools (40), divisional secretariat (40) and hospital (40) in Nintavur. The measuring tool was modified questionnaire of Hayman (2005) which consisted of 15 questions. Data were subjected to descriptive statistics. The results of the study revealed that the level of work life balance of employees attached to government schools, divisional secretariat, and hospital in Nintavur was moderate level.